Role of Solanum wild species in potato improvement - Sood, Salej; Bhardwaj, Vinay; Kardile, Hemant; Dalamu, Dalamu (Indian Horticulture, 2020)
The cultivated potato, Solanum tuberosum L. (2n=4x=48) is an important part of people’s diet. It belongs to family Solanaceae and genus Solanum having nearly 200 tuber bearing species. As per latest estimates, the potato germplasm resource is composed of 107 wild relatives, four landrace cultivated species and modern cultivars. Although most cultivated potatoes are tetraploid, nearly three-fourth of wild species are diploid. Wild potatoes are mostly distributed in Andean highlands, which is the centre of origin of potato. There are abundant reports of disease and pest resistance in wild species of potato.